1982
DOI: 10.1111/j.1365-2621.1982.tb05007.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Doses of High and Low Intensity UV Irradiation on Surface Microbiological Counts and Storage‐Life of Fish

Abstract: Ultraviolet (UV) irradiation at 254 nm and doses of 300 mWs/cm* from a photochemical reactor (16.6 mm at 300 pW/cm*) or 4.8 Ws/cm* from a high intensity UVC lamp (40 set at 120-180 mW/cm* reduced surface microbial count on mackerel by two to three log cycles. UV treated mackerel wrapped in 1 mil polyethylene and packed in -1°C ice had at least a 7 day longer shelf life than conventional ice-packed untreated controls. Spray washing with water containing 10 ppm chlorine by itself or in combination with W irradia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 7 publications
1
26
0
1
Order By: Relevance
“…The roughness of the LDPE surface can decrease UV radiation efficiency, because the bactericidal effect occurs only in the direction of the radiation beam (6). In this study, the LDPE microtopography surface analysis ( Fig.…”
Section: Discussionmentioning
confidence: 87%
“…The roughness of the LDPE surface can decrease UV radiation efficiency, because the bactericidal effect occurs only in the direction of the radiation beam (6). In this study, the LDPE microtopography surface analysis ( Fig.…”
Section: Discussionmentioning
confidence: 87%
“…irradiation. Huang and Toledo (1982), investigating the inactivation of the natural microbial flora on the skin of whole fish by u.v., showed that u.v. was more effective in inactivating micro-organisms on the skin of smooth-surfaced fish, such as mackerel, than on rough-surfaced fish, such as mullet.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, u.v. has also been proposed for the surface disinfection of a wide range of materials including fish (Huang and Toledo 1982), meat and poultry (Stermer et al 1987;WallnerPendleton et al 1994), contact lenses (Dolman and Dobrogowski 1989) particulate matter (Shama et al 1994), and the surfaces of egg shells (Kuo et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…UV light's potential in destroying bacteria, viruses and parasites has been documented by many researchers (Bintsis, Litopoulou-Tzanetaki, & Robinson, 2000;Chang et al, 1985;Demirci, 2002;Dunn, Ott, & Clark, 1995;Harm, 1980;Huang & Toledo, 1982;Rowan, MacGregor, Anderson, Fouracre, & Farish, 1999;Shechmeister, 1983;Sommers, Sites, & Musgrove, 2010). Like many of its counterpart decontamination technologies, UV light has destructive effect on bacteria which is attributed to many reasons.…”
Section: Ultraviolet Irradiationmentioning
confidence: 94%